On zeros of the characteristic polynomial of matroids of bounded tree-width. (February 2017) - Chun, Carolyn; Hall, Rhiannon; Merino, Criel; Noble, Steven
Abstract: We develop some basic tools to work with representable matroids of bounded tree-width and use them to prove that, for any prime power q and constant k, the characteristic polynomial of any loopless, G F ( q ) -representable matroid with tree-width k has no real zero greater than q k − 1 .